Perioperative myocardial infarction during coronary artery bypass grafting. The main approaches to diagnosis and prevention - Yu. A. Argunova; M. V. Larionov (Российский кардиологический журнал)
The incidence of perioperative complications, including perioperative myocardial damage and infarction, remains high with the increasing number of coronary artery bypass grafting (CABG) performed worldwide. These conditions are predictors of poor prognosis in the postoperative period. Therefore, it is relevant to develop strict diagnostic criteria for these conditions and to search for optimal preventive measures.Cardioprotection is used at all stages of patient management in the perioperative period after CABG. The comprehensive approach containing preoperative management of the patient (prehabilitation), intraoperative cardioprotection and risk factor management in the postoperative period is considered to be the most effective one.The review presents current approaches to the diagnosis of myocardial infarction after CABG, as well as the basic concepts of its prevention at all stages of patient management.